DE-ACIDIFICATION OF CRUDE OIL USING IONIC LIQUIDS - SHAH, SYED NASIR (2016)
In this study, N-alkyl imdazolium ionic liquids with highly alkaline phenolate anions were used for the removal of naphthenic acid from model acid oil. The liquid-liquid equilibrium (LLE) data for the ternary mixture of [C,mim][Phe], dodecane and naphthenic acid were experimentally obtained at a constant temperature of 303.15 K and atmospheric pressure.